Comparison Of Smartphones Using Data Envelopment Analysis. - Mustafa, Adli; Tan, Lean Peaw (2005)
In today's digital era, competition for smart gadgets is often fierce. The last few years have witnessed the emergence of smartphones with each manufacturer trying to out do its competitor in terms of attractive features.